2009
DOI: 10.1111/j.1865-1682.2008.01052.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Risk of PRRSV Transmission via Ingestion of Muscle from Persistently Infected Pigs

Abstract: The objectives of this experiment were to determine how long porcine reproductive and respiratory syndrome virus (PRRSV) could be detected in muscle tissues of experimentally infected pigs and to evaluate the transmissibility of PRRSV to pigs via ingestion of quantitative reverse-transcriptase polymerase chain reaction (qRT-PCR)-positive muscle tissues. Serum, lymphoid tissues, and muscle (M. longissimus dorsi) samples were collected from 135 pigs (89 PRRSV-inoculated pigs and 46 negative control). Between 28 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 14 publications
(22 reference statements)
0
5
0
1
Order By: Relevance
“…Lung homogenates from each pig were tested by real-time PCR for PRRSV and PRCV RNA quantification as previously described (Jung et al , 2007; Molina et al , 2008). For PRRSV, all samples were tested at the Animal Disease Research and Diagnostic Laboratory, Veterinary Science Department, South Dakota State University, USA.…”
Section: Methodsmentioning
confidence: 99%
“…Lung homogenates from each pig were tested by real-time PCR for PRRSV and PRCV RNA quantification as previously described (Jung et al , 2007; Molina et al , 2008). For PRRSV, all samples were tested at the Animal Disease Research and Diagnostic Laboratory, Veterinary Science Department, South Dakota State University, USA.…”
Section: Methodsmentioning
confidence: 99%
“…Studies on the infectivity of PRRS virus-infected pork are limited, and only four studies have been published (van der Linden et al, 2003a;Magar and Larochelle, 2004;Cano et al, 2007;Molina et al, 2009). The earliest work done in the Netherlands used twenty-four 8-week-old-pigs as sources of infected muscle for an oral exposure trial (van der Linden et al, 2003a).…”
Section: Infectivity Of Prrs Virus-positive Porkmentioning
confidence: 99%
“…In a large study conducted in the United States, eighty‐nine 14‐day‐old piglets were inoculated with 10 4 TCID 50 of PRRS virus strain MN‐184 by intramuscular injection (Molina et al., ). An additional 56 piglets were sham‐inoculated with MEM by intramuscular injection.…”
Section: Isolation Of Prrs Virus From Musclementioning
confidence: 99%
“…However, Molina et al (29) further investigated the transmissibility of PRRS by ingestion of meat from infected animals, and reported that, while 13 of 89 muscle samples (14.6%) were positive for PRRS by RT-PCR at various intervals post infection, in none of these 13 cases did the feeding of 100 g to 200 g of meat to individually housed recipient pigs result in infection.…”
Section: Feeding Trialsmentioning
confidence: 99%